Respuesta :

Answer:

The correct answer is A. x = - 9

Step-by-step explanation:

Let's solve the equation:

5x + 8 − 3x = −10

5x - 3x = - 10 - 8

2x = - 18

x = - 9 (Dividing by 2 at both sides of the equation)

Now let's prove the answer is correct, replacing x with - 9.

5x + 8 − 3x = −10

5 (-9) + 8 - 3 (-9) = - 10

-45 +8 - 27 = - 10

-45 + 35 = - 10

-10 = - 10

It has proven the value of x = - 9 is correct

The correct answer is A. x = - 9

Answer:

a

Step-by-step explanation:

ACCESS MORE